Basic researchCo-culture with Schwann cells is an effective way for adipose-derived stem cells neural transdifferentiation - Liao, Dapeng; Gong, Ping; Li, Xiaojie; Tan, Zhen; Yuan, Quan (Archives of Medical Science, 2010)
Introduction: Adipose-derived stem cells (ADSCs) could accomplish neural transdifferentiation with the presence of certain growth factors in vitro . It has been proved that bone marrow stromal cells (BMSCs) can realize neural transdifferentiation only by being co-cultured with Schwann cells (SCs), and in our former studies we have confirmed that ADSCs could do so too. This paper aims to investigate whether the neural induction efficiency of co-culture is as high as that of other strategies using chemicals or chemicals combined with some growth factors. Material and methods: We isolated and multiplied ADSCs from adult Sprague-Dawley rats, and SCs from sciatic nerves of 1-to-2-day-old Sprague-Dawley rat pups, then induced ADSCs neural transdifferentiation through 2% dimethyl sulphoxide (DMSO) and DMSO combined with growth factors. Meanwhile we co-cultured ADSCs and SCs in Transwell culture dishes without intercellular contacts. Immunostaining and RT-PCR were adopted to investigate the neural transdifferentiation of ADSCs. Then we compared the expression differences for genes S100, nestin and GFAP of the above three protocols by real-time PCR. Results: Both immunostaining and RT-PCR proved that ADSCs could accomplish neural transdifferentiation through each of the above three protocols. And real-time PCR further shows that the gene expression relative quantities for the above three genes are not statistically different between co-culture and induction through DMSO combined with growth factors (p > 0.05), but both of them are statistically different from induction only by DMSO (p < 0.05). Conclusions: Co-culturing ADSCs and SCs may be a simple, effective and practical way for ADSCs neural transdifferentiation.